FRITJOF CAPRA'S PHILOSOPHY IN ANALYZING A SCIENCE FOR SUSTAINABLE LIVING, ECOLOGICAL LITERACY AND CLIMATE CHANGE - Irwan, Irwan; Zusmelia, Zusmelia; Siska, Felia; Husnita, Liza; Melia, Yenni; Elvawati, Elvawati (Universitas Tanjungpura, 2023)
The focus of the study in this paper analyzes Fritjof Capra's thoughts on A Science For Sustainable Living, Ecological Literacy and Climate Change This research uses a qualitative approach and the Ex Post Facto analysis method. The method of data collection in this study was carried out by direct observation in the field, literature study through reading sources such as journals, books and analyzing with YouTube playing related topics, namely Fritjof Capra. The results of this study show that the concept of A Science for Sustainable Living is related to human actions and ecosystems. Human actions in utilizing nature must not interfere with the existing ecosystem. So Ecological Literacy is important for humans to have the ability to understand the principles of organization, human life systems and use guidelines in creating sustainable societies or humans. This ability and understanding of humans has the power to think in predicting climate change and reducing residual burning that has a global impact.